Architects, Bandits and Knights - Lidin, Konstantin (project baikal, 2006)
Some quotations: «A new disaster has been added to pollution of the unique lake–it is cottage development of the coast». «The trouble is that the projects are realized without even being seen by architectural society. Including the objects on the coast of Lake Baikal. We took Sergey Kiselev to see one of such objects, it was a halfcompleted building. Like other Moscow colleagues he admitted that it was an obviously conceited excess. In general almost every object recently built in Listvyanka represents a burst of excess… What is happening here with architecture and urban planning is absolutely inadmissible».«Current capital development at Lake Baikal visually pollutes the coast, bringing alien elements to the landscape and view (for example, the cottages of pseudorussian style and cabin cars)».Acting as a client of architectural and design project Russian mafia has a number of individual characteristics.Firstly, an ordinary businessman is childishly confident that the architect's (or designer's) work is a very interesting and fascinating stuff. He believes that this work gives lots of pleasure and entirely consists of creative discoveries and triumph.By the way already ancient Greeks considered creativity to be a sort of Eros. So the mafia client is eager to take part in such a pleasant thing. In spite of expressing his wishes clearly and giving the way to the professional, the client strives for being both a participant and a coauthor of the project. At best he is constantly bothering the architect with many pieces of advice and «valuable suggestions ». At worst the project, which is already finished, approved and even paid, is altered by the client during the process of its realization, while the author is not even informed about it. The building completed, the shocked architect sees a monster that has arisen from his project as a result of «the editing».Secondly, any typical Mafioso finds it very important to persistently exhibit his aggressiveness and readiness to start the struggle end even to die. The cult of physical strength and defiance of danger is one of fundamental principles of the mafia corporate culture. The client's drive to provoke a quarrel and to explain «who is the boss» makes the relations between the architect and the client very peculiar.Thirdly, a productive labour interdiction is another important feature of traditional mafia culture. This view is a variation of the famous «idle class» ethos brilliantly described by Veblen Thorstein in his classic work. The ethics of the members of the idle class, which is also called by Veblen a «predatory class», forbids them to work or to be involved in any productive labour. Instead it allows them to fight, to govern the state and to go in for sport. From the point of view of the predatory culture there are only two types of people. The first one includes warriors, fighters and bandits, they arouse «fair» emotions of anger and fury as rivals or companionsinarms on the field of battle. The second type is represented by bastards, brutes and plough cattle, they are worth nothing but contempt. Most citizens' opinion on the building is of no importance. Only what the respected people of the same type, that is mafia «good guys», say (or think) about it is taken into account.The tendencies to erect such incongruous and ugly buildings on the coast of Lake Baikal can hardly be stopped easily and quickly. Those tendencies have very deep roots. They are based, though in a perverted and wry manner, on the old traditions of Siberian culture. So it is senseless to struggle, to forbid and to show anger and contempt towards an uncultured wilful client. As well as it is no good to have «what can I do for you?» attitude and to follow all the whims of the predatory class.